A STUDY OF CHANGES IN THE SPATIAL STRUCTURE OF BITUNG CITYBASED ON INDICATORS OF PEOPLE MOVEMENT PATTERNS, RELATED TO THE COVID-19 PANDEMIC - Tangkudung, Fitri Meylinda; Rogi, Octavianus H. A.; Siregar, Frits O. P. (SPASIAL, 2021)
Bitung City, as an urban area, is characterized as a cluster of built-up areas that are relatively dense and has several residential concentration clusters and high-density service centre points scattered in several zones. So, in theoretical understanding, the city of Bitung is allegedly identified as a Polycentric city. However, when the covid-19 pandemic occurred, the city of Bitung became one of the affected. The spread of exposed areas in the city was relatively fast and provided a traumatic experience for the community. This traumatic experience also encourages changes in people's perceptions, preferences, and behaviour in travelling both within the city and in and out of the city. Undoubtedly, there has been a significant change in the daily movement patterns of local people during this pandemic in the city of Bitung. Changes in the pattern of a community movement that occurred must have impacted changes in the spatial structure of Bitung City. The purpose of the study was to identify whether or not there was a change in the type of spatial structure in Bitung City based on indicators of daily movement patterns of local people in the Period before the pandemic, the peak of the pandemic, and after the peak of the pandemic whether the change will be permanent or temporary, and identify problems based on existing conditions and associative spatial policies with the type of spatial structure of Bitung City in the future in the post-pandemic era. The analysis method was the Origin-Destination Survey method with the division of the Travel Destination Survey questionnaire and comparing based on 3 (three) pandemic times such as 1) The Period Before the Pandemic; 2) The peak of the pandemic; and 3 (three) Period After pandemic peak. The results showed that (1) The shape of Bitung city space structure in the Period before the pandemic and after the peak of the pandemic tended to be in the form of a polycentric model, while at the peak of the pandemic, the city of Bitung tended to be in the form of a Monocentric model; (2) There were several urban problems that the city of Bitung must face as a city with a tendency of Polycentric Cities based on existing conditions, and some problems during the covid-19 pandemic but not continuously.Keywords : Spatial Structure, Daily Movement Patterns, Origin Destination